The Influence Of Transformational Leadership, Digital Competence, And Employee Engagement On The Performance Of Government Employees At The Panai Tengah \Subdistrict Office - Firmansyahputra Harahap; Muhammad Irwansyah Hasibuan; Mhd. Amin (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
. Employee performance in public sector organizations is increasingly influenced by leadership practices, digital capabilities, and employee involvement, particularly in the context of rapid digital transformation. Subdistrict offices, as the frontline of public services, are required to adapt to technological changes while maintaining effective organizational management. This study aims to examine the effect of transformational leadership, digital competence, and employee engagement on employee performance at the Panai Tengah Subdistrict Office. A quantitative research approach was employed using a survey method. Data were collected through structured questionnaires distributed to employees of the Panai Tengah Subdistrict Office, with a total of 80 respondents involved in this study. The collected data were analyzed using multiple linear regression analysis, including partial tests, simultaneous tests, and coefficient of determination analysis. The results of the study reveal that, partially, transformational leadership does not have a significant effect on employee performance, indicating that leadership practices implemented in the organization have not yet directly influenced individual performance outcomes. Employee engagement, which was measured through internal communication, also does not show a significant effect on employee performance, suggesting that existing communication patterns have not fully encouraged active participation and commitment among employees. In contrast, digital competence has a positive and significant effect on employee performance, demonstrating that employees’ ability to utilize digital technology, manage information, and operate digital tools effectively plays a crucial role in enhancing work productivity and performance quality. Simultaneously, transformational leadership, digital competence, and employee engagement have a significant effect on employee performance. The coefficient of determination indicates that a large proportion of employee performance variation can be explained by the independent variables examined in this study. These findings imply that strengthening digital competence, supported by effective leadership and improved employee engagement, is essential for improving employee performance in public sector organizations.